2022
DOI: 10.1111/fcp.12806
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of gender‐affirming hormonal therapy in transgender persons: Assessing reports in the French pharmacovigilance database

Abstract: Limited data are available on adverse drug reactions (ADRs) of gender‐affirming hormone therapy (HT), mainly due to the lack of population‐based studies with adequate controls, thus making spontaneous reporting systems a valuable tool to detect potential side reactions. In this nationwide retrospective study, we aimed to analyze ADRs related to gender‐affirming HT reported in the French pharmacovigilance database (FPVD). We requested all the individual case safety reports related to gender‐affirming HT recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Another cohort of 2555 patients reported significantly increased incidences of meningioma and prolactinoma compared with the general female population (standardized incidence ratios 11.9; CI 95% [5.5–22.7] and 26.5; CI 95% [12.9–48.6] respectively) 38 . Recently, Yelehe et al 39 showed that meningiomas were the principal reported ADRs in French M‐to‐F transgenders, followed by cardiovascular events, with a median time to onset of 5.3 months. All these data confirm the real necessity to closely monitor M‐to‐F patients with “off‐label” high and long progestogen treatments, for whom discontinuation of treatment is also particularly challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Another cohort of 2555 patients reported significantly increased incidences of meningioma and prolactinoma compared with the general female population (standardized incidence ratios 11.9; CI 95% [5.5–22.7] and 26.5; CI 95% [12.9–48.6] respectively) 38 . Recently, Yelehe et al 39 showed that meningiomas were the principal reported ADRs in French M‐to‐F transgenders, followed by cardiovascular events, with a median time to onset of 5.3 months. All these data confirm the real necessity to closely monitor M‐to‐F patients with “off‐label” high and long progestogen treatments, for whom discontinuation of treatment is also particularly challenging.…”
Section: Discussionmentioning
confidence: 99%